Polymorphs, salts, and cocrystals: what's in a name? - Aitipamula, Srinivasulu; Banerjee, Rahul; Bansal, Arvind K.; Biradha, Kumar; Cheney, Miranda L.; Choudhury, Angshuman Roy; Desiraju, Gautam R.; Dikundwar, Amol G.; Dubey, Ritesh; Duggirala, Nagakiran; Ghogale, Preetam P.; Ghosh, Soumyajit; et al. (Crystal Growth & Design, 2012)
The December 2011 release of a draft United States Food and Drug Administration (FDA) guidance concerning regulatory classification of pharmaceutical cocrystals of active pharmaceutical ingredients (APIs) addressed two matters of topical interest to the crystal engineering and pharmaceutical science communities: (1) a proposed definition of cocrystals; (2) a proposed classification of pharmaceutical cocrystals as dissociable ``API-excipient'' molecular complexes. The Indo U.S. Bilateral Meeting sponsored by the Indo-U.S. Science and Technology Forum titled The Evolving Role of Solid State Chemistry in Pharmaceutical Science was held in Manesar near Delhi, India, from February 2-4, 2012. A session of the meeting was devoted to discussion of the FDA guidance draft. The debate generated strong consensus on the need to define cocrystals more broadly and to classify them like salts. It was also concluded that the diversity of API crystal forms makes it difficult to classify solid forms into three categories that are mutually exclusive. This perspective summarizes the discussion in the Indo-U.S. Bilateral Meeting and includes contributions from researchers who were not participants in the meeting.

Polymorphs, salts and cocrystals: what's in a name? (vol 12, pg 2147, 2012) - Aitipamula, Srinivasulu; Banerjee, Rahul; Bansal, Arvind K.; Biradha, Kumar; Cheney, Miranda L.; Choudhury, Angshuman Roy; Desiraju, Gautam R.; Dikundwar, Amol G.; Dubey, Ritesh; Duggirala, Nagakiran; Ghogale, Preetam P.; Ghosh, Soumyajit; et al. (Crystal Growth & Design, 2012)

Ferromagnetic tetranuclear Cu(II) complex: catecholase and phenoxazinone synthase activities - Mitra, Merry; Kundu, Tanay; Kaur, Gurpreet; Sharma, Gyaneswar; Choudhury, Angshuman Roy; Singh, Yogesh; Ghosh, Rajarshi (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: catalysis; Ferromagnetic; Tetranuclear copper

Catecholase and phenoxazinone synthase activities of a ferromagnetically coupled tetranuclear Cu(II) complex - Mitra, Merry; Kundu, Tanay; Kaur, Gurpreet; Sharma, Gyaneswar; Choudhury, Angshuman Roy; Singh, Yogesh; Ghosh, Rajarshi (RSC Advances, 2016)
A crystallographically characterized tetranuclear Cu(II) complex [Cu-4(II)(L)(4)] (1) [H2L = N-(2-hydroxyethyl)-3-methoxysalicylaldimine] is found to show overall ferromagnetic exchange coupling. Complex (1) mimics the catalytic activity of the plant enzyme catechol oxidase by oxidising 3,5-di-tert-butylcatechol to its corresponding quinone in methanol and dichloromethane medium in the presence of aerial oxygen. The reaction follows Michaelis-Menten enzymatic reaction kinetics with turnover numbers (K-cat) 6.99 x 10(3) and 1.85 x 10(3) h(-1) in methanol and dichloromethane, respectively. 1 is also phenoxazinone synthase active in methanol medium with a turnover number of 1.21 x 10(5) h(-1).

Structure-property correlation of halogen substituted benzothiazole crystals - Thekkeppat, Nipun P.; Singla, Labhini; Tothadi, Srinu; Das, Priyadip; Choudhury, Angshuman Roy; Ghosh, Soumyajit (Journal of Molecular Structure, 2021)
We have synthesized 3 benzothiazole crystals (1-3) based on existing knowledge of combining flexibility and optical properties towards achieving applications for flexible optoelectronics. However, one crystal was found to be elastically bendable and was found to comply necessary packing features for elasticity. Other two crystals do not obey packing features for elasticity hence they are brittle in nature. Further, Hirshfeld analysis illustrates that elastic crystal 1 possess more number of weak and dispersive interactions compared to other crystals. These interactions were instrumental in invoking elasticity. Moreover, crystals 1-3 were found to be fluorescent as well at specific excitation wavelengths. Therefore, among these crystals, particularly crystal 1 is considered as more promising candidate for flexible optoelectronics. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Benzothiazole crystals; Elasticity; Halogen bond; mechanical properties

DNA binding, antitubercular, antibacterial and anticancer studies of newly designed piano-stool ruthenium(ii) complexes - Navale, Govinda; Singh, Sain; Agrawal, Sonia; Ghosh, Chandrachur; Choudhury, Angshuman Roy; Roy, Partha; Sarkar, Dhiman; Ghosh, Kaushik (Dalton Transactions, 2022)
The chemotherapeutic potential of ruthenium(ii) complexes has recently attracted researchers' interest as antibacterial and anticancer agents. In this study, two novel half-sandwich imine-based Ru complexes ([Ru(p-cymene)Cl(L-1)][PF6] (Ru-1) and [Ru(p-cymene)Cl(L-2)][PF6] (Ru-2)) were reported for their deoxyribonucleic acid (DNA) binding and antitubercular, antibacterial, and anticancer activities. The molecular structure of Ru-2 was obtained by single-crystal X-ray crystallography. DNA interaction studies were conducted by UV-Vis absorbance and fluorescence spectral titration which gave rise to DNA binding constants (K-b) of 1.32 x 10(6) and 1.82 x 10(6) for Ru-1 and Ru-2, respectively and the Stern-Volmer binding constant (K-SV) values for Ru-1 and Ru-2 were 1.7763 x 10(4) M-1 and 7.6 x 10(3) M-1, respectively. The in vitro antitubercular activity was evaluated against Mycobacterium tuberculosis H37Ra. The antibacterial potential of both the Ru-complexes was examined against Gram-negative (Escherichia coli and Pseudomonas aeruginosa) and Gram-positive (Staphylococcus aureus and Bacillus subtilis) bacteria. The half-maximal inhibitory concentration (IC50) values for the antitubercular activity of Ru-1 and Ru-2 were 4.87 +/- 1.32 mu M and 5.78 +/- 0.54 mu M, respectively. A cytotoxic study of these complexes was performed against the human breast cancer cell line (MCF-7) and the human embryonic kidney cell line (HEK293) (normal cells). The study revealed meaningful activity of the Ru-1 complex against (cancer) MCF-7 cells, while the viability of HEK293 (normal) cells in the presence of Ru-2 was higher as compared to a reference drug 5FU. We suggest that these kinds of Ru-complexes could have potential for application in metallopharmaceuticals.